Modified Dijkstra Shortest Path Algorithm for SD Networks - Abdelghany, Haitham; Zaki, Fayez; Ashour, Mohammed (International Journal of Electrical and Computer Engineering Systems, 2022)
This paper uses a modified Dijkstra shortest path method for considering cumulative delays rather than bandwidth in software-defined networks. To implement the proposed method, an open-source Ryu controller is used, and a Mininet tool is used to emulate the topology. The proposed method is compared with the traditional Dijkstra’s algorithm to demonstrate its performance. This comparison shows that the modified Dijkstra’s algorithm provides higher performance of the different cumulative delays. Several experiments were conducted to evaluate the performance of the proposed method using three parameters (bandwidth, transfer rate and jitter). In addition, the cumulative distribution function is calculated using the parameters to show its distribution through the experiment period.